Singapore the encyclopedia - Koh, Tommy (Editions didier Millet, 2006)
Singapore: The Encyclopedia contains over 2,500 alphabetically arranged entries on a vast range of topics -- practically everything the general reader might want to know about Singapore, four decades after the achievement of full independence.